Transformation of Chronic Myeloid Leukemia to Acute Undifferentiated Leukemia: Case Report and Literature Review - Oussama Grari; Assya Khermach; Nouhaila Chahid; Nisma Douzi; Amina Himri; Abdelilah Berhili; Mounia Slaoui; Nabiha Trougouty; Mohammed Bensalah; Rachid Seddik (Journal of Applied Hematology)
Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm driven by the BCR::ABL1 fusion gene and typically progresses through chronic, accelerated, and blast crisis phases. While blast crises often present with myeloid or lymphoid phenotypes, transformation to acute undifferentiated leukemia (AUL) is exceedingly rare and presents significant diagnostic and therapeutic challenges. We describe a 41-year-old female with CML whose disease transformed to AUL during blast crisis. Initially treated with imatinib, therapy was discontinued due to loss of response, followed by a brief, intolerant course of nilotinib. After 2 years without treatment, she presented with general deterioration, anemia, and splenomegaly. Laboratory findings revealed hyperleukocytosis, severe thrombocytopenia, and 27% undifferentiated blasts on peripheral blood smear; bone marrow aspiration confirmed 53% blasts with negative myeloperoxidase staining. Immunophenotyping confirmed AUL, showing blasts with weak CD45 expression, CD34 positivity, HLA-DR positivity, and absence of lineage-specific markers, whereas cytogenetic analysis revealed a complex karyotype. The patient was treated with a 3 + 7 chemotherapy regimen but developed infectious complications, ultimately succumbing to cardiovascular arrest. This case highlights the complexity and poor prognosis of atypical CML transformations. It underscores the need for a deeper understanding of blast crisis mechanisms and innovative therapeutic strategies to improve patient care and outcomes.